Dental magnetic resonance imaging for bone loss assessment and disease activity classification in severe periodontitis - Lauer, Arne; Schulte, Luisa; Skenderi, Artid; Tekiki, Nouha; Jürchott, Alexander; Sohani, Meysam; Rütters, Maurice; Schwindling, Franz Sebastian; Rammelsberg, Peter; Nittka, Mathias; Heiland, Sabine; Bendszus, Martin; et al. (Insights into imaging, 2025)
To evaluate the reliability and accuracy of dental MRI (dMRI) for volumetric infrabony and furcation bone loss compared to cone-beam computed tomography (CBCT) and to correlate to clinical signs of inflammation in patients with severe periodontitis.